ASOSIASI JENIS BURUNG DI TAMAN WISATA ALAM WERA KECAMATAN DOLO BARAT KABUPATEN SIGI BIROMARU SULAWESI TENGAH - Abd Manan Al Raja Denda; Annawaty Annawaty; Moh Ihsan; Ramadhanil Pitopang (Biology Department, Mathematics and natural science, Tadulako University, 2018)
Association of bird species in Wera Nature Park, had been done from March to April 2016. This research aimed to discover the association among bird species existing in Wera Nature Park of West Dolo Sub-District of Sigi Regency of Central Sulawesi. The method used was transect method, which was by making plots measuring 20x20 m totaling 15 plots and were placed along the transect line with a length of 50 m. To find the relationship among the species, the researcher used association analysis which were counted based on the 2x2 contingency table. The result was then confirmed by using X² Chi-square table. Based on the analysis result, it can be found that there are seven associations formed, namely tricoloured munia (Lonchura malacca) and the lemon-bellied white-eye (Zosterops chloris) bird species, collared kingfisher (Halcyon chloris) and yellow-billed malkoha (Phaenicophaeus calyorhinchus), sooty-headed bulbul (Pynonotus aurigaster) and lemon-bellied white-eye (Zosterop schloris), lemon-bellied white-eye (Zosterops chloris) and rusty-breasted cuckoo (Cacomantis sepulclaris), yellow-billed malkoha (Phaenicophaeus calyorhinchus) and uniform Swiftlet (Colacalia vanikorensis), white-necked myna (Streptocitta albicollis) and brahminy kite (Haliastur indus), tricoloured munia (Lonchura malacca) and rusty-breasted cuckoo (Cacomantis sepulclaris).